The «Silver lining» methodology to develop strategic excercises about future scenarios - Castillo Chamorro, José Miguel (Journal of the Spanish Institute for Strategic Studies, 2021)
Innovation consists of producing new and more effective solutions to old problems, thanks to the technological development. Nowadays, many prospective projects still use methods and techniques that belong to the past century, consequently many think-tanks are still solving old problems with old methods. In this article we are going to introduce an example of innovation in the field of the strategic analysis of future scenarios. The Silver lining methodology is designed to help strategic analysts envision and analyze the set of possible future scenarios that can influence upon the development of a strategic plan. Silver lining is an agil methodology that implement a metric to ensure the quality of prospective exercises as well as a fast obtention and elaboration of the data elicited from each human expert. We use Artificial Intelligence procedures to process human experts’ opinions and gathering all of them in the single answer of a group. The methodology has been validated by the performance of several prospective exercices led by the Spanish Institute of Strategic Studies.
Keywords: Strategy; foresight; methodology; futures scenarios; innovation